Controversies on Timing of Sex Assignment and Surgery in Individuals With Disorders of Sex Development: A Perspective - Tatiana Prade Hemesath; Tatiana Prade Hemesath; Leila Cristina Pedroso de Paula; Leila Cristina Pedroso de Paula; Clarissa Gutierrez Carvalho; Clarissa Gutierrez Carvalho; Julio Cesar Loguercio Leite; Julio Cesar Loguercio Leite; Guilherme Guaragna-Filho; Guilherme Guaragna-Filho; Eduardo Corrêa Costa; Eduardo Corrêa Costa (Frontiers Media S.A., 2019)
Appropriate management of disorders of sex development (DSD) has been a matter of discussion since the first guidelines were published in the 1950s. In the last decade, with the advent of the 2006 consensus, the classical methods, especially regarding timing of surgery and sex of rearing, are being questioned. In our culture, parents of DSD newborns usually want their children to undergo genital surgery as soon as possible after sexual assignment, as surgery helps them to confirm the assigned sex. Developmental psychology theories back this hypothesis. They state that anatomic differences between sexes initiate the very important process of identification with the parent of the same sex. Sex-related endocrinological issues also demand early care. For example, using dihydrotestosterone cream to increase penile length or growth hormone treatment to improve final height require intervention at young ages to obtain better results. Although the timing of surgery remains controversial, recent evidence suggests that male reconstruction should be performed between 6 and 18 months of age. Feminizing surgery is still somewhat controversial. Most guidelines agree that severe virilization requires surgical intervention, while no consensus exists regarding mild cases. Our perspective is that precocious binary sex assignment and early surgery is a better management method. There is no strong evidence for delays and the consequences can be catastrophic in adulthood.